When Sex is Work: Organizing for Labour Rights and Protections - van der Meulen, Emily (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2012)
Research on sex work has documented the harmful effects of criminalization on sex workers’ safety. Despite this body of research, the effects of criminalization on the organization of labour within the sex industry and sex workers’ suggestions for labour improvements have been largely ignored. In part, this is due to the mostly hypothetical nature of sex work labour organizing, as many common work-related activities are illegal. When one cannot work from a fixed location, have a manager or employer, or communicate about the terms and conditions of services, focusing on labour improvements can become secondary to protecting oneself from criminal charges. However, the 2010 Ontario Superior Court ruling to decriminalize aspects of prostitution opens the door for a more nuanced analysis of sex work as a form of labour and for the development of diverse labour organizing strategies. This article presents narratives from a qualitative study with ten current and former sex workers and two allies. It begins by highlighting interviewees’ arguments in favour of a “sex is work” paradigm before presenting their suggestions for workplace improvements and ideas about effective labour organizing efforts.